Big balloon race, (The) - Coerr, Eleanor ([s.l.] : HarperCollins, 1992)
Ariel almost causes her famous mother to lose a balloon race and he helps her to win it.
Originally published : New York, N.Y : Harper & Row, 1981.
Keywords: Myers, Carlotta, 1849-1932.; Myers, Ariel -- Juvenile fiction; Balloon ascencions -- Fiction